Analysis of Customer Satisfaction on Quality of Jakarta Corridor MRT (Mass Rapid Transit) Service 1 (Lebakbulus Station - Bundaran HI) - Ari Hesti Purnomo; Amar Mufhidin (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Seeing the very high mobility behavior of the Jakarta people and difficult to avoid congestion, it is appropriate, a solution that invites people to move from private vehicles to mass transportation modes such as the Jakarta MRT. The transportation service industry is an interesting sector to observe because Jakarta MRT is relatively new transportation in Jakarta. This study aims to determine the level of passenger satisfaction with the quality of Jakarta Corridor 1 MRT services (Lebak bulus Station - HI Roundabout) reviewed using the questionnaire method, using 100 respondents taken randomly from Lebak Bulus to the HI Roundabout and vice versa. To get the results of customer satisfaction required data on the average rating of respondents and the results obtained an average value above 3 and included in the category of very satisfied according to the CSI table. To get data that needs to be a priority to be improved and data that needs to be maintained the level of service quality needs to be tested using the Cartesian diagram of the importance- performance method and the results of data that become priorities for improvement are safety aspects at trains and stations as well as courtesy of officers. To test the results of the analysis conducted a validity test using the bivariate correlation method to measure the validity and invalidity of the data with a significance value of 1% and R tables obtained at 0.258 and 100% validity results (all valid data), reliability testing to measure the level of consistency of respondents in filling out the questionnaire from the SPSS program counting process gets the result that the questionnaire has a high level of consistency.